Reliable Techniques for Data Transfer in Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2014)
Reliable delivery of data is a key challenge in Wireless Sensor Networks (WSN). This paper discusses various challenges to achieve data reliability. Various data transport protocols that deliver data in both upstream and downstream directions are discussed in detail. Furthermore the existing data transport reliability protocols are analyzed based on various reliability levels. Techniques based on retransmission and redundancies are discussed. Retransmission techniques seem to be efficient but leads to overhead. Redundancy techniques like erasure code, Reed Solomon codes and route fix seems to be the best alternative in a resource constrained WSN. Finally it has been stated that the right combination of retransmission and redundancy techniques helps to achieve high reliability. On the basis of the analysis, few research challenges to achieve reliability are pointed out.